Avaliação do nível de satisfação no trabalho e dos sintomas de Burnout em docentes da área da saúde - Dallacosta, Fabiana Meneghetti (2014)
Teaching is considered a high risk profession of stress and exhaustion, which makes teachers susceptible to physical and mental diseases, as the burnout syndrome. This cross-sectional study, quali-quantitative, aimed to evaluate the job satisfaction and burnout in health´s teachers from two private universities in southern Brazil, using the questionnaires OSI and MBI, respectively. In total, 139 teachers participated in this study 51.1% women, average age 44.05 (± 9.5) years, average time of teaching 11.7 (± 8.4) years. Most (56,8%) have job satisfaction, 41.8% partially satisfied and 1.4% dissatisfied. The highest satisfaction scores were on items motivation, relationship and content of work, and dissatisfaction were workload and supervision. About burnout, 13.7% have the syndrome, being more frequent in women and teachers with lower age and less teaching time.